1995
DOI: 10.1016/0735-1097(95)00311-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hemodynamic improvement after reperfusion during right ventricular infarction

Abstract: Reperfusion in the setting of right ventricular infarction leads to rapid hemodynamic improvement and may result in improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…5,8,11,12 Of 165 patients screened, 40 were excluded because of technically inadequate echocardiographic images, leaving 125 patients analyzed in this study who underwent emergency coronary angiography according to standard techniques. 8,[13][14][15] …”
Section: Methodsmentioning
confidence: 99%
“…5,8,11,12 Of 165 patients screened, 40 were excluded because of technically inadequate echocardiographic images, leaving 125 patients analyzed in this study who underwent emergency coronary angiography according to standard techniques. 8,[13][14][15] …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, without a doubt reperfusion therapy should be applied by any method in this high-risk entity. [27][28][29] …”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to the studies of Roth A et al [10] and Tabone X et al [11] which suggested thrombolytic therapy was of little benefit in improving RV function early after MI. In another study by Kinn et al, [12] there was rapid improvement in haemodynamics only in patients with successful reperfusion of the infarct related artery after thrombolytic therapy. Probably failed reperfusion or early stunning of RV might have contributed to these findings in our study.…”
Section: Discussionmentioning
confidence: 99%